2017
DOI: 10.1101/211599
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

INFERNO - INFERring the molecular mechanisms of NOncoding genetic variants

Abstract: The majority of variants identified by genome--wide association studies (GWAS) reside in the noncoding genome, where they affect regulatory elements including transcriptional enhancers.We propose INFERNO (INFERring the molecular mechanisms of NOncoding genetic variants), a novel method which integrates hundreds of diverse functional genomics data sources with GWAS summary statistics to identify putatively causal noncoding variants underlying association signals. INFERNO comprehensively infers the relevant tiss… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 64 publications
(68 reference statements)
1
32
0
Order By: Relevance
“…Moreover, development of PTSD biomarkers have focused on the stress response, peripheral inflammation (inflammatory cytokines, C‐reactive protein), neural‐immune communication, 55 and response of the blood immune cells to glucocorticoid activation 53 . Collectively, the results of the current study support and extend the previously suggested role of the immune system and regulation of cell activation in both LOAD 10,56‐60 and PTSD 61,62 …”
Section: Discussionsupporting
confidence: 82%
“…Moreover, development of PTSD biomarkers have focused on the stress response, peripheral inflammation (inflammatory cytokines, C‐reactive protein), neural‐immune communication, 55 and response of the blood immune cells to glucocorticoid activation 53 . Collectively, the results of the current study support and extend the previously suggested role of the immune system and regulation of cell activation in both LOAD 10,56‐60 and PTSD 61,62 …”
Section: Discussionsupporting
confidence: 82%
“…Genome-wide association studies (GWASs) have successfully identified over 70,000 genetic variants associated with more than 3,000 human diseases and phenotypes (Buniello et al, 2019). Interpretation of these associations remain difficult (Watanabe et al, 2017;Amlie-Wolf et al, 2018) as most GWAS hits are in the noncoding genome. Resolution of GWAS is limited as neighboring variants have similar associations due to linkage disequilibrium (LD) (Amlie-Wolf et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of these associations remain difficult (Watanabe et al, 2017;Amlie-Wolf et al, 2018) as most GWAS hits are in the noncoding genome. Resolution of GWAS is limited as neighboring variants have similar associations due to linkage disequilibrium (LD) (Amlie-Wolf et al, 2018). Our recently developed INFERNO method (Amlie-Wolf et al, 2018) focuses on identifying potentially causal variants underlying observed GWAS associations by integrating with hundreds of functional genomics datasets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The database is currently undergoing a major overhaul and will eventually be superseded by POSTGAP . A valid and recent alternative is INFERNO 23 , though it does only rely on eQTL data for target gene assignment. These resources implement some or all of the approaches that will be reviewed in the workflow and constitute good entry points for identifying the most likely target gene(s) of regulatory SNPs.…”
Section: Introductionmentioning
confidence: 99%